Myc coordinates transcription and translation to enhance transformation and suppress invasiveness. (4th November 2015) - Elkon, Ran; Loayza‐Puch, Fabricio; Korkmaz, Gozde; Lopes, Rui; van Breugel, Pieter C; Bleijerveld, Onno B; Altelaar, AF Maarten; Wolf, Elmar; Lorenzin, Francesca; Eilers, Martin; Agami, Reuven
Abstract: c‐Myc is one of the major human proto‐oncogenes and is often associated with tumor aggression and poor clinical outcome. Paradoxically, Myc was also reported as a suppressor of cell motility, invasiveness, and metastasis. Among the direct targets of Myc are many components of the protein synthesis machinery whose induction results in an overall increase in protein synthesis that empowers tumor cell growth. At present, it is largely unknown whether beyond the global enhancement of protein synthesis, Myc activation results in translation modulation of specific genes. Here, we measured Myc‐induced global changes in gene expression at the transcription, translation, and protein levels and uncovered extensive transcript‐specific regulation of protein translation. Particularly, we detected a broad coordination between regulation of transcription and translation upon modulation of Myc activity and showed the connection of these responses to mTOR signaling to enhance oncogenic transformation and to the TGFβ pathway to modulate cell migration and invasiveness. Our results elucidate novel facets of Myc‐induced cellular responses and provide a more comprehensive view of the consequences of its activation in cancer cells. Synopsis: This study reports the effect of Myc induction on gene expression at the levels of transcription, translation and protein amounts at a genomic scale, and uncovers novel facets of regulation carried out by this major proto‐oncogene. Transcriptional regulation and modulation of translation efficiency in response to Myc activation are broadly coordinated. Myc‐induced pathways that enhance oncogenic transformation are mediated by mTOR. Myc activation suppresses numerous ECM and adhesion genes at both the transcriptional and protein translation levels to attenuate cell motility and invasiveness. TGFβ suppresses Myc expression and reverses its effect on ECM and adhesion gene expression and on cell motility and invasiveness. Abstract : This study reports the effect of Myc induction on gene expression at the levels of transcription, translation and protein amounts at a genomic scale, and uncovers novel facets of regulation carried out by this major proto‐oncogene.